Pengaruh Lingkungan Kerja, Fasilitas, Disiplin Kerja, dan Beban Kerja Terhadap Kinerja Pegawai pada Kantor Desa Meranti Omas Kabupaten Labura - Lily Paradina Nainggolan; Bayu Eko Broto; Christine Herawati Limbong (Postgraduate, University of Mataram, 2023)
The purpose of this study was to determine partially and simultaneously how the influence of the work environment, comfort, work discipline, and workload of the Meranti Omas District Office on employee performance. This research was conducted in Kab. Meranti Omas Labura Village Office during January and February 2023. This research is quantitative in nature and uses data analysis techniques using SPSS 25.0 For Windows software. The results of instrument testing include validity, reliability, traditional assumptions, multiple linear regression, and determinants (t, F, and R2). The author chose a sample of 15 people from the study population which consisted of all employees at the village office. The results showed that the work environment had a positive and substantial effect on employee performance, with a regression coefficient of 1.260 (signed positive) and sig 0.000 (0.05). Facilities have a significant and positive effect on employee performance, with a regression coefficient of 0.909 (signed positive) and sig 0.000 (0.05). Work discipline has a positive and substantial effect on employee performance as indicated by a regression coefficient of 0.294 (positive sign) and sig 0.000. (0.05). Workload and employee performance have a correlation coefficient of 0.243 (positive sign) and 0.000 (0.05) respectively. Employee performance is influenced by work environment, facilities, work discipline, and workload, with a coefficient of determination of 6.923 and a significance value of 0.000 (0.05). The result of analytic adjustment (R2) is 0.712 or 71.2%, while the remaining 28.8% is influenced or explained by other variables not examined in this study